2019
DOI: 10.3390/en12142754
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Comparison of Coastal Wind Speeds between WRF Simulations Using Different Input Datasets in Japan

Abstract: In order to improve the accuracy of the wind speed simulated by a mesoscale model for the wind resource assessment in coastal areas, this study evaluated the effectiveness of using the Japan Meteorological Agency (JMA)’s latest and finest (2 km × 2 km) grid point value (GPV) data, produced from the local forecast model (LFM) as input data to the mesoscale model. The evaluation was performed using wind lidar measurements at two sites located on the coasts of the Sea of Japan and Pacific Ocean. The accuracy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…It was hoped that by selecting the periods simulated in this manner (as has been done in other resource assessment sensitivity studies [22,32]), the effect of major seasonal changes on annual winds would be captured by the options being tested. The grid nudging option of the WRF Four-Dimensional Data Assimilation (FDDA) system is a technique that has been used in several studies on wind downscaling for resource assessment purposes [20,52,53]. The technique bridges the gap between the model simulations and time-interpolated values from input data.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…It was hoped that by selecting the periods simulated in this manner (as has been done in other resource assessment sensitivity studies [22,32]), the effect of major seasonal changes on annual winds would be captured by the options being tested. The grid nudging option of the WRF Four-Dimensional Data Assimilation (FDDA) system is a technique that has been used in several studies on wind downscaling for resource assessment purposes [20,52,53]. The technique bridges the gap between the model simulations and time-interpolated values from input data.…”
Section: Experimental Designmentioning
confidence: 99%
“…The technique bridges the gap between the model simulations and time-interpolated values from input data. All three simulation domains were nudged during all the simulations, following practices of previous studies [20,52,53]. Nudging options and simulation lengths were chosen based on recommendations from a previous study in coastal Ghana [49].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that accuracy of WRF output varies with input data, which can be roughly classified into three types: (a) atmospheric data (e.g. Akimoto and Kusaka 2010;Carvalho, Rocha, and Gómez-Gesteira 2012;Misaki et al 2019), (b) topography and land use (e.g. Cheng et al 2013;Jee and Kim 2016;Jiménez-Esteve et al 2018;Mallard, Spero, and Taylor 2018;Kikuchi, Fukushima, and Ishihara 2020), and (c) sea surface temperature (SST) as a lower boundary condition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that local winds were simulated accurately and realistically when atmospheric input data that are representative of local conditions were used. Misaki et al (2019) conducted WRF simulations using three atmospheric datasets to evaluate accuracy of WRF simulated wind speeds above the sea surface in Niigata and Ibaraki, Japan. Kikuchi, Fukushima, and Ishihara (2020) conducted WRF simulations for the area around the offshore observation station (meteorological mast) at Choshi, Japan to evaluate the effect of replacing the land use dataset from the US Geological Survey (USGS) by the high resolution dataset provided by the National Land Information Division.…”
Section: Introductionmentioning
confidence: 99%